PERKEMBANGAN FONOLOGI PADA ANAK DALAM PROSES AKUISISI BAHASA ARAB: KAJIAN PSIKOLINGUISTIK - Faizzatin Isnaini; Hanik Mahliatussikah (Tarling : Journal of Language Education, 2025)
This study analyzes children's phonological development in acquiring Arabic as a second language through a psycholinguistic approach. Arabic phonology presents high complexity, involving distinctive sounds not found in a child's native language, such as hijaiyah letters. Literature reviews reveal that phonological skills are influenced by internal factors, such as biological abilities and innate mechanisms (Language Acquisition Device), as well as external factors, including learning environments and teaching methods. Findings highlight key challenges in pronouncing hijaiyah letters, which can be addressed through multisensory approaches, the use of educational technology, and supportive learning environments. This study also emphasizes the importance of integrating phonology and semantics on arabic teaching. Holistic and adaptive learning strategies are recommended to effectively support Arabic language acquisition.